PENGARUH LITERASI KEUANGAN, SIKAP KEUANGAN, KEPRIBADIAN, DAN PENDAPATAN TERHADAP PERILAKU PENGELOLAAN KEUANGAN UMKM KULINER DI KECAMATAN MEDAN PETISAH - Br Sembiring, Emninta; Pasaribu, Juwita Aknesia; Br Sinaga, Jholant Bringg Luck Amelia; Br Sembiring, Veramika (POLITEKNIK LP3I JAKARTA, 2026)
This study examines the impact of financial literacy, financial attitudes, personality, and income on financial management behavior among culinary MSME actors in Medan Petisah Sub-District. A quantitative causal design was employed, with the population comprising all MSMEs in the sub district. Samples were selected via purposive sampling based on criteria aligned with the study's objectives. Data were collected through a Google Form-based questionnaire from 100 respondents and analyzed using SPSS version 22. Findings reveal that financial literacy (sig. 0.000 < 0.05; t count = 9.015), financial attitudes (sig. 0.001 < 0.05; t-count = 3.555), personality (sig. 0.034 < 0.05; t-count = 2.154), and income (sig. 0.005 < 0.05; t-count = 2.891) each significantly influence financial management behavior. Collectively, these factors exert a substantial effect, underscoring their crucial role in financial management.